1‐Undecene from Pseudomonas aeruginosa is an olfactory signal for flight‐or‐fight response in Caenorhabditis elegans. (4th June 2021) - Prakash, Deep; MS, Akhil; Radhika, Buddidhathi; Venkatesan, Radhika; Chalasani, Sreekanth H; Singh, Varsha
Abstract: Animals possess conserved mechanisms to detect pathogens and to improve survival in their presence by altering their own behavior and physiology. Here, we utilize Caenorhabditis elegans as a model host to ask whether bacterial volatiles constitute microbe‐associated molecular patterns. Using gas chromatography–mass spectrometry, we identify six prominent volatiles released by the bacterium Pseudomonas aeruginosa . We show that a specific volatile, 1‐undecene, activates nematode odor sensory neurons inducing both flight and fight responses in worms. Using behavioral assays, we show that worms are repelled by 1‐undecene and that this aversion response is driven by the detection of this volatile through AWB odor sensory neurons. Furthermore, we find that 1‐undecene odor can induce immune effectors specific to P . aeruginosa via AWB neurons and that brief pre‐exposure of worms to the odor enhances their survival upon subsequent bacterial infection. These results show that 1‐undecene derived from P . aeruginosa serves as a pathogen‐associated molecular pattern for the induction of protective responses in C . elegans . Synopsis: The volatile molecule 1‐undecene produced by Pseudomonas aeruginosa activates a pathogen‐specific immune response in Caenorhabditis elegans resulting in the activation of flight or fight response. 1‐undecene volatile produced by P. aeruginosa activates flight response in C. elegans on short time scale of second to minutes. Longer exposure of worms to 1‐undecene induces a pathogen‐specific immune response. Both flight and fight response induced by 1‐undecene rely on the AWB olfactory neurons of worms. Preexposure of worms to 1‐undecene protects them against a subsequent infection with P. aeruginosa . 1‐Undecene serves as a pathogen‐associated molecular pattern (PAMP) for C. elegans . Abstract : Identification of volatile bacterial compounds reveals 1‐undecene as a microbe‐associated molecular pattern detected by nematode odor sensory neurons to promote avoidance behavior and induces expression of specific immune effectors.